Steiner formula and Holditch-Type Theorems for homothetic Lorentzian motions - Yuce, S.; Kuruoglu, N. (SHIRAZ UNIV, 2007)
The present paper is concerned with the generalization of the Holditch Theorem under one-parameter homothetic motion on Lorentzian planes. In this paper, for the homothetic Lorentzian motion, we expressed the Steiner formula. Furthermore, we present the Holditch-Type Theorems.
Keywords: holditch theorem; steiner formula; lorentzian plane; homothetic motion; Science & Technology - Other Topics